Evaluation of the effectiveness of blood-drop agglutination test for chicken tuberculosis diagnosis - M. O. Baratov (Ветеринария сегодня)
Due to the increased role of opportunistic infections, mycobacterioses, parasitocenoses, etc. the detectability of nonspecific reactions to PPD-tuberculin has sharply increased, which makes it difficult to make a diagnosis and brings laboratory test methods to the fore. The aim of the study was to determine practical significance of blood-drop agglutination test in comparison with allergy test, and frequency of avian tuberculosis lesions on internal organs. For comparative assessment of these techniques 4,086 chickens were tested, including 2,000 young chicks aged 6–9 months and 2,086 adult poultry. In order to compare the results of allergy and serological tests, necropsy was performed for reacting chickens, identified using blood-drop agglutination test and demonstrating positive results using both methods. Low effectiveness of the allergy test in comparison with the serological test was established. The blood-drop agglutination test made it possible to additionally identify 311 adult chickens seropositive for tuberculosis in poultry farms. The effectiveness of this serological method in young birds and poor matching of results in comparison with an allergy test have been shown. The necropsy findings confirmed the practical significance of the serological test; generalized tuberculosis process was noted in all birds positively reacting in blood-drop agglutination test. The dependence of internal organ lesions on poultry-keeping conditions was determined in tuberculosis-affected farms in the autumn and spring periods. Internal organ lesions were found in 835 birds out of 1,072 tested poultry. In the autumn period the intestines were affected in most cases (57.2%), lung lesions were found in the least cases (8.2%), and in the spring period tuberculosis lesions were more often detected in the lungs (43.8%), less often in the intestines (35.5%). In the winter period, the morbidity predominantly occurs due to dust infection, and in summer, birds become infected via alimentary route, which explains the results obtained. The identification of a significantly larger number of diseased chickens, both in advanced form and at an early stage, makes it possible to recommend a blood-drop agglutination test for the diagnosis of tuberculosis. The involvement of internal organs directly depends on the poultry keeping system and should be taken into account when veterinary and sanitary measures are performed.